The Outlaw Machine, the Monstrous Outsider and Motorcycle Fetishists: Challenging Rebellion, Mobility and Masculinity in Kenneth Anger’s Scorpio Rising and Steven Spielberg’s Duel - Boczkowska, Kornelia (Text Matters: A Journal of Literature, Theory and Culture, 2019)
The paper analyzes the ways in which Kenneth Anger’s Scorpio Rising (1963) and Steven Spielberg’s Duel (1971) draw on and challenge selected road movie conventions by adhering to the genre’s traditional reliance on cultural critique revolving around the themes of rebellion, transgression and roguery. In particular, the films seem to confront the classic road movie format through their adoption of nomadic narrative structure and engagement in a mockery of subversion where the focus on social critique is intertwined with a deep sense of alienation and existential loss “laden with psychological confusion and wayward angst” (Laderman 83). Following this trend, Spielberg’s film simultaneously depoliticizes the genre and maintains the tension between rebellion and tradition where the former shifts away from the conflict with conformist society to masculine anxiety, represented by middle class, bourgeois and capitalist values, the protagonist’s loss of innocence in the film’s finale, and the act of roguery itself. Meanwhile, Anger’s poetic take on the outlaw biker culture, burgeoning homosexuality, myth and ritual, and violence and death culture approaches the question of roguery by undermining the image of a dominant hypermasculinity with an ironic commentary on sacrilegious and sadomasochistic practices and initiation rites in the gay community. Moreover, both Duel’s demonization of the truck, seen as “an indictment of machines” or the mechanization of life (Spielberg qtd. in Crawley 26), and Scorpio Rising’s (homo)eroticization of a motorcycle posit elements of social critique, disobedience and nonconformity within a cynical and existential framework, hence merging the road movie’s traditional discourse with auteurism and modernism.